2000
DOI: 10.1007/bf02479924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged nonpulsatile left heart bypass on vascular control status

Abstract: We investigated the vascular control status, including vasoactive hormones, systemic vascular resistance (SVR), and baroreceptor sensitivity, in prolonged nonpulsatile left heart bypass (NLHB). Nine goats underwent pulsatile left heart bypass (PLHB) with a ventricular assist device (VAD). Two weeks postoperatively, the VAD was replaced with a centrifugal pump and NLHB was subsequently conducted for 4 weeks. Thirteen healthy goats were also evaluated to obtain normal control data. The aortic pulse pressure on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In this study, during NLHB, mAoP did not show any extreme oscillations, and SVR, systemic blood flow, and major vasoactive hormone levels maintained a level of consistency; hence, it was inferred that the baroreceptor function was maintained during NLHB. Previously, we evaluated the baroreceptor function and reported the maintenance of the baroreceptor function during NLHB as well as the levels of normal control animals and the level of animals during PLHB (25). Therefore, the cause of the reduction in SVR reaction was not likely to have been the downgrading of the baroreceptor function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, during NLHB, mAoP did not show any extreme oscillations, and SVR, systemic blood flow, and major vasoactive hormone levels maintained a level of consistency; hence, it was inferred that the baroreceptor function was maintained during NLHB. Previously, we evaluated the baroreceptor function and reported the maintenance of the baroreceptor function during NLHB as well as the levels of normal control animals and the level of animals during PLHB (25). Therefore, the cause of the reduction in SVR reaction was not likely to have been the downgrading of the baroreceptor function.…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic change in the hemodynamic parameters was a decrease in pulse pressure, observed while continuous flow left heart bypass was performed for 4 weeks. The pulse pressure of the Continuous Flow Group (11 ± 4 mm Hg) was clearly lower than that of the normal healthy goats (37 ± 4 mm Hg) (8). Both the bypass flow (105 ± 8 ml/min/kg) and the mean aortic pressure (104 ± 4 mm Hg) in the Continuous Flow Group were maintained within approximately the normal range (8).…”
Section: Resultsmentioning
confidence: 76%
“…There are 3 possible mechanisms for the diminution of vasoconstrictive function: a change in vascular SMCs, a change in the desensitization of vascular α‐receptors, and a change in baroreceptor function. Previous studies have demonstrated that baroreceptor function is maintained during continuous flow left heart bypass (10,18). This narrows the list of possible mechanisms to 2.…”
Section: Discussionmentioning
confidence: 94%